TEKNOLOGI TERAPAN PENGHALAU BURUNG OTOMATIS BAGI PETANI PADI DI SALINGKA KAMPUS UNIVERSITAS ANDALAS - Eka Candra Lina; Zaini Zaini; Yesi Puspita (Jurnal Hilirisasi IPTEKS, 2018)
West Sumatra is a province where the average population works as a farmer. Rice production in West Sumatra is quite high, reaching 55,532 tons per year. However, farmers experience difficulties in dealing with pest attacks, one of which is bird pest. Bird pest causes a loss of yield of 30% and even 100% at severe levels of attack, and in other cerelia plants capable of causing yield loss to reach 67%. As a result of high yield loss, it is necessary to control bird pests. However, control of bird pests is not the same as other pests that can be controlled practically using pesticides due to mobile pests that are mobile or active. t present farmers still use mechanical control in Sumatra called 'Manggaro'. Where farmers wait for their fields and fields during the filling phase until harvest. This mechanical control takes the time of the farmer to drive the arrival of bird pests. Based on these problems, it takes a business and technology that can be used to drive birds without the need to be monitored by farmers, save time and be more efficient in controlling and can be used in the long run. The proposed research activities included the installation of automatic bird removal equipment with a body heat detection system and sound source swinging motor in the paddy fields located at the Unand Limau Manis campus. Observations made were the results of rice production on the 3 treatments given, namely the use of automatic pest removal tools,